DESIGN OF TANDON AND AUTOMATIC FILLING TOOLS ON DISPENSERS WITH ULTRASONIC SENSORS - Hafizt Azzari Aldaf; Indyah Hartami Santi; Yusniarsi Primasari (Universitas Islam Balitar, 2019)
Nowdays, The development of water dispensers has hot and cold water technology, but fills water into cold and hot water storage tanks by lifting and putting the gallons on top of the dispenser so that water can flow into hot and cold water storage tanks, this is assessed less efficient. The purpose of making this tool is to make it easier for users to install gallons without having to lift the gallon and put it on top of the reservoir, it can also facilitate the taking of drinking water without having to press or open the faucet first. Because in modern era, the need for tools that work automatically and efficiently are increasing. The results of this study indicate that automatic water and faucet filler devices in dispensers using ultrasonic sensors as a whole work well and are in accordance with the function specified. The function of the ultrasonic sensor is as a reader the maximum limit of water level in the reservoir, so that when the water is in its maximum state, the pump will stop filling the reservoir. And the ultrasonic sensor in front of the dispenser functions to read the glass, the sensor will detect and then be received by the microcontroller and continue to execute the relay and open the selenoid so that the water can come out.